Oxytocin promotes bone formation during the alveolar healing process in old acyclic female rats - Colli, Vilma Clemi [UNESP]; Okamoto, Roberta [UNESP]; Spritzer, Poli Mara; Dornelles, Rita Cássia Menegati [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Objective: OT was reported to be a direct regulator of bone mass in young rodents, and this anabolic effect on bone is a peripheral action of OT. The goal of this study was to investigate the peripheral action of oxytocin (OT) in the alveolar healing process in old female rats.Materials and methods: Females Wistar rats (24-month-old) in permanent diestrus phase, received two ip (12 h apart) injections of saline (NaCl 0.15 M - control group) or OT (45 mu g/rat - treated group). Seven days later, the right maxillary incisor was extracted and analyses were performed up to 28 days of the alveolar healing process (35 days after saline or OT administration).Results: Calcium and phosphorus plasma concentrations did not differ between the groups. The plasma biochemical bone formations markers, alkaline phosphatase (ALP) and osteocalcin were significantly higher in the treated group. Histomorphometric analyses confirmed bone formation as the treated group presented the highest mean value of post-extraction bone formation. Tartrate-resistant acid phosphatase (TRAP) was significantly reduced in the treated group indicating an anti-resorptive effect of OT. Immunohistochemistry reactions performed in order to identify the presence of osteocalcin and TRAP in the bone cells of the dental socket confirmed these outcomes.Conclusions: OT was found to promote bone formation and to inhibit bone resorption in old acyclic female rats during the alveolar healing process. Published by Elsevier Ltd.
Keywords: Bone regeneration; Oxytocin; Tooth extraction; Aging